TRAINING OF CADETS OF SPECIAL FORCES UNITS USING TRAINING TOOLS IN HAND-TO-HAND COMBAT TRAINING - Rakhmetov Takhir Tolaganovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the content of the hand-to-hand combat program as a military-practical part of the physical training of cadets at a higher educational institution, and the current state of hand-to-hand combat training of cadets of various higher educational institutions.